Challenges and opportunities for improving eco-efficiency of tropical forage-based systems to mitigate greenhouse gas emissions - Peters, Michael; Herrero, Mario; Fisher, M.; Erb, Karlheinz; Rao, Idupulapati M.; Subbaraoa, Guntur V.; Castro, A.; Arango, Jacobo; Chara, J.; Murgueitio, E.; Hoek, Rein van der; Läderach, Peter R.D.; et al. (New South Wales Department of Primary Industry, 2013)
Forage-based livestock production plays a key role in national and regional economies, for food security and poverty alleviation. Livestock production is also considered as a major contributor to agricultural GHG emissions, however. While demand for livestock products is predicted to continue to increase, there is political and societal pressure both to reduce environmental impacts and to convert some of the pasture area to alternative uses such as crop production and environmental conservation. Thus it is essential to develop approaches for sustainable intensification of livestock systems to mitigate GHG emissions, addressing biophysical, socioeconomic and policy challenges. This paper highlights the potential of improved tropical forages in crop-livestock systems, and linked with policy incentives, to enhance livestock production while reducing its environmental footprint. We give examples for sustainable intensification to mitigate GHG emissions based on improved forages in Brazil and Colombia and suggest future perspectives.